Faktor-Faktor Yang Mempengaruhi Perilaku Pembelian Konsumen (Studi pada Toko Oli Lancar Widodo Semarang) - Prasetyo, Teguh; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
This study aimed to determine the factors that influence consumer purchasingbehavior at Lancar Widodo Store Semarang. This research used the subject data. In this case thesubject of the research was consumers of Lancar Widodo Store Semarang. This study usedConvenience sampling or aese, which means respondents were the buyers of oil products with nocriteria found by the researcher at Lancar Widodo Store Semarang. The number of samples was100 people. The data analysis technique used was multiple linear regression. The results showedthat the culture had no influence on consumer purchasing behavior, social had no influence onconsumer purchasing behavior, personal influenced the consumer purchasing behavior, andpsychology had no influence on consumer purchasing behavior. While simultaneously culture,social, personal, psychology influenced the consumer purchasing behavior.Keywords: culture, social, personal, psychology.